2023
DOI: 10.24938/kutfd.1143318
|View full text |Cite
|
Sign up to set email alerts
|

A New Inflammation Marker in Rheumatoid Arthritis: Immature Granulocyte

Abstract: Objective: This study aimed to reveal whether immature granulocyte levels can be used for determining the disease activity of rheumatoid arthritis. Material and Methods: The study was conducted in the Kastamonu Rehabilitation Center. The data of 163 patients with rheumatoid arthritis were reviewed retrospectively. Laboratory data of 92 healthy individuals were used for the control group. Complete blood cell counts, measurement of erythrocyte sedimentation rate, and C-reactive protein level were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In this study, similar to the study reported by Özcan et al., 27 it was found that the number of IG and IG% were higher in RA patients than in healthy controls, and there was a positive relationship between IG, ESR, and CRP. Unlike that study, 27 it was found that IG# and IG% were independent diagnostic determinants of RA. In this study, disease activity was determined by DAS28.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, similar to the study reported by Özcan et al., 27 it was found that the number of IG and IG% were higher in RA patients than in healthy controls, and there was a positive relationship between IG, ESR, and CRP. Unlike that study, 27 it was found that IG# and IG% were independent diagnostic determinants of RA. In this study, disease activity was determined by DAS28.…”
Section: Discussionsupporting
confidence: 92%
“…It was stated that DAS28 and also other RA disease activity indexes (CDAI, and SDAI) were not evaluated in the study and that studies evaluating the relationship between DAS28 and IGs are needed 27 . In this study, similar to the study reported by Özcan et al., 27 it was found that the number of IG and IG% were higher in RA patients than in healthy controls, and there was a positive relationship between IG, ESR, and CRP. Unlike that study, 27 it was found that IG# and IG% were independent diagnostic determinants of RA.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations